STRATEGI TUTOR DALAM MENINGKATKAN MINAT BELAJAR WARGA BELAJAR PROGRAM PENDIDIKAN KESETARAAN PAKET C PADA MASA PANDEMI COVID-19 DI PKBM KAK SETO PEKANBARU - Kesumawardhani, Rossa Diah; Wilson, Wilson; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the Tutor's Strategy in Increasing the Learning Interest of the Learning Community of the Package C Equality Education Program During the Covid-19 Pandemic At PKBM Kak Seto Pekanbaru. The results showed that the strategies adopted by tutors in increasing the learning interest of learning residents during the covid-19 pandemic at PKBM Kak Seto Pekanbaru were as follows: (1) presenting the designed material (in the form of systematically compiling content and presenting material in a lesson plan), ( 2) provide stimulation (in the form of encouragement in the form of motivational words, games so that citizens learn to be enthusiastic again in participating in the learning process), (3) develop regular habits (form good habits), (4) improve the physical condition of learning residents (pay attention to and maintaining good communication), (5) providing supporting facilities in the learning process. This study aims to describe the tutor's strategy in increasing the learning interest of learning residents during the covid-19 pandemic at PKBM Kak Seto Pekanbaru. This type of research is descriptive with a qualitative approach, in which the data collection process is carried out by interviewing 3 subjects, namely control informants, core informants 1 and core informants 2 with documentation included. Based on the results of interviews, researchers found 3 indicators, namely: (1) Learning Objectives, (2) Characteristics of Students, (3) Learning Supporting Facilities/Learning Media. The study of these 3 indicators is very useful for understanding how the Tutor's Strategy in Increasing the Learning Interest of Residents in Learning the Package C Equality Education Program During the Covid-19 Pandemic At Pkbm Kak Seto Pekanbaru.Key Words: Tutor Strategy, Learning Interests of Learning Citizens, Equality Education Program Package C